Domestic Violence among Married Women in Baghdad City - Kadhum Zeidan, Muna Abdul (Diyala Journal of Medicine, 2019)
Background: Violence against women is a worldwide problem and serious human rights abuse that occurs among all social, cultural, economic and religious groups. Objective: To assess of domestic violence among sample of married women and to determine relationship between the domestic violence among married women and some related factors such as (age, education level of wife, wife employment, and monthly income. Subjects and Methods: A cross-sectional Descriptive analysis processed of study among of married women in Baghdad city. The sample was selected by (non-probability convenient sampling) and sample size was (400). The study started from 1St April 2014 to 31th of March 2015. The data was collected by direct interview using special questionnaire to obtained socio-demographic information. Results: The result shows that mean age of the subjects was 29.7 ± 6.65 years, 45.8% were housewives, economic problems, and cultural, psychological problems were reported were the commonest reasons for domestic violence. Analysis of results by Frequency, percentage, mean of score, standard deviation, and relative Sufficiency, Factors found to be significantly associated with overall violence were: lower educational level, had higher levels of unemployment, type of family, lower income and having children. Conclusions: The research concluded that the women exposure from emotional or psychological violence more than physical and sexually violence.